Gut microbiota associated with HIV infection is significantly enriched in bacteria tolerant to oxygen. Issue 1 (1st July 2016) - Dubourg, Grégory; Lagier, Jean-Christophe; Hüe, Sophie; Surenaud, Mathieu; Bachar, Dipankar; Robert, Catherine; Michelle, Caroline; Ravaux, Isabelle; Mokhtari, Saadia; Million, Matthieu; Stein, Andreas; Brouqui, Philippe; et al.
Abstract : Objectives: Gut microbiota modifications occurring during HIV infection have recently been associated with inflammation and microbial translocation. However, discrepancies between studies justified a comprehensive analysis performed on a large sample size. Design and methods: In a case–control study, next-generation sequencing of the 16S rRNA gene was applied to the faecal microbiota of 31 HIV-infected patients, of whom 18 were treated with antiretroviral treatment (ART), compared with 27 healthy controls. 21 sera samples from HIV-infected patients and 7 sera samples from control participants were used to test the presence of 25 markers of inflammation and/or immune activation. Results: Diversity was significantly reduced in HIV individuals when compared with controls and was not restored in the ART group. The relative abundance of several members of Ruminococcaceae such as Faecalibacterium prausnitzii was critically less abundant in the HIV-infected group and inversely correlated with inflammation/immune activation markers. Members of Enterobacteriaceae and Enterococcaceae were found to be enriched and positively correlated with these markers. There were significantly more aerotolerant species enriched in HIV samples (42/52 species, 80.8%) when compared with the control group (14/87 species, 16.1%; χ 2 test, p<10 −5, conditional maximum-likelihood estimate (CMLE) OR=21.9). Conclusions: Imbalance between aerobic and anaerobic flora observed in HIV faecal microbiota could be a consequence of the gut impairment classically observed in HIV infection via the production of oxygen. Overgrowth of proinflammatory aerobic species during HIV infection raises the question of antioxidant supplementation, such as vitamin C, E or N -acetylcysteine.